Estimation Of Coal Resources Using the Method Polygon In Bulungan Regency North Kalimantan Province - Anshariah, Anshariah; Bintang Akbar , Achmed; Ardianto Budiman, Agus (Journal of Geology and Exploration, 2022)
This research was conducted at one of the national companies engaged in coal mining. The Mining Business Permit (IUP) area in Bulungan Regency, North Kalimantan Province, has an area of 1,000 Ha Mining Business Permit (IUP). The purpose of this research is to find out the average thickness of coal and the measurable resources of coal and its tonnage. The polygon method is a calculation with the basic concept, which states that a certain point represents all sediment characteristics of an area. The data needed in this study are survey data, geological data, collar data, thickness, and topographic data (str). From observational data in the field, 31 drill logs were obtained with an average drill log depth of 6.75 meters with a measured volume of coal resources of 33,341,065 and a measured tonnage of coal resources of 50,711,759 MT, with a density of (1.3 tonnes/m3).